1994
DOI: 10.1111/j.1467-8543.1994.tb01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Performing for Pay? The Effects of ‘Merit Pay’ on Motivation in a Public Service

Abstract: Original citation:Marsden, David and Richardson, Ray (1994) Performing for pay? The effects of 'merit pay' on motivation in a public service. British Journal of Industrial Relations, 32 (2). pp. 243-261. ISSN 1467-8543 DOI: 10.1111/j.1467-8543.1994.tb01043.x © 1994 This version available at: http://eprints.lse.ac.uk/4030/ Available in LSE Research Online: January 2016 LSE has developed LSE Research Online so that users may access research output of the School. Copyright © and Moral Rights for the papers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 4 publications
5
112
2
10
Order By: Relevance
“…Alguns pesquisadores têm examinado atitudes dos empregados em relação à política de incentivo de desempenho (MARSDEN; RICHARDSON, 1994;KELLOUGH;SELDEN, 1997;MAMMAN, 1998). O interesse principal dos pesquisadores concentra-se em como estes sistemas de incentivo afetam a motivação e desempenho dos empregados (KOHN, 1993;MARSDEN;RICHARDSON, 1994;MANOLOPOULOS, 2008).…”
Section: Recompensas E Desempenhounclassified
See 1 more Smart Citation
“…Alguns pesquisadores têm examinado atitudes dos empregados em relação à política de incentivo de desempenho (MARSDEN; RICHARDSON, 1994;KELLOUGH;SELDEN, 1997;MAMMAN, 1998). O interesse principal dos pesquisadores concentra-se em como estes sistemas de incentivo afetam a motivação e desempenho dos empregados (KOHN, 1993;MARSDEN;RICHARDSON, 1994;MANOLOPOULOS, 2008).…”
Section: Recompensas E Desempenhounclassified
“…O interesse principal dos pesquisadores concentra-se em como estes sistemas de incentivo afetam a motivação e desempenho dos empregados (KOHN, 1993;MARSDEN;RICHARDSON, 1994;MANOLOPOULOS, 2008). Locke et al (1980) argumentam que o dinheiro é um incentivo crucial e que nenhum outro incentivo ou técnica motivacional alcança o valor instrumental do dinheiro.…”
Section: Recompensas E Desempenhounclassified
“…En Angleterre, Marsden et Richardson (1994) ont trouvé que la rémunération au mérite n'a pas les effets attendus sur la motivation des agents dans un centre d'impôts. En effet, si les salariés adhèrent à l'idée de la rému-nération des performances et estiment pouvoir atteindre le niveau de rendement exigé, la plupart considère que l'atteinte de leurs objectifs n'entraîne pas une récom-pense particulière ou entraîne une récompense trop faible pour constituer une incitation suffisante.…”
Section: Les éTudes Menées Dans Le Secteur Public Des éTats-unis De unclassified
“…Marsden and Richardson (1994) found that 26% of their sample of Inland Revenue staff reported that performance-related pay had made them less willing to assist colleagues. A follow-up study by Marsden and French (1998) found that, despite management attempts to deal with some of the earlier disadvantages of the scheme, this percentage had risen to 63%.…”
Section: Competition Instead Of Co-operationmentioning
confidence: 99%
“…(p.69) There are other public sector jobs with hard to measure outcomes, however, where performancerelated pay has been introduced and its motivational effect observed. Marsden and Richardson (1994) studied the effects of the introduction of performance-related pay into the Inland Revenue and found that staff did not report that their motivation had improved. Asked if performancerelated pay had led them to change in line with a range of objectives such as improve the quality or quantity of their work, work harder or give sustained high performance, a large majority replied negatively.…”
Section: Motivationmentioning
confidence: 99%